A synopsis of the genus Cylindrostethus Fieber 1861 (Insecta: Hemiptera: Gerridae) - Floriano, Carla Fernanda Burguez; Bispo, Pitágoras Da Conceição [UNESP]; Moreira, Felipe Ferraz Figueiredo (Springer Nature, 2024)
Cylindrostethus Fieber, 1861 is one of the most striking genera of water striders (Insecta: Hemiptera: Gerridae) and has Pantropical distribution. Members of this group can be recognized by the very long, cylindrical body; the short antennomere IV; the short labium not reaching the mesosternum; and by characteristics of the abdomen of males and females. Although Neotropical representatives of the genus have been revised, there are pending taxonomic issues related to this fauna, and that of the Eastern Hemisphere has been barely studied in recent years. Here, we present a short note about the authorship of Cylindrostethus, an updated key to all species of the genus, a new synonymy, and the description of a previously unknown macropterous male of C. hungerfordi Drake and Harris.
Keywords: Aquatic insects; Cylindrostethinae; Gerromorpha; Semiaquatic bugs; Water striders